Antarctic glaciers export carbon-stabilised iron(II)-rich particles to the surface Southern Ocean - Rhiannon L. Jones; Jon R. Hawkings; Michael P. Meredith; Maeve C. Lohan; Oliver W. Moore; Robert M. Sherrell; Jessica N. Fitzsimmons; Majid Kazemian; Tohru Araki; Burkhard Kaulich; Amber L. Annett (Nature Communications)
Abstract Iron is an essential micronutrient for phytoplankton and plays an integral role in the marine carbon cycle. The supply and bioavailability of iron are therefore important modulators of climate over glacial-interglacial cycles. Inputs of iron from the Antarctic continental shelf alleviate iron limitation in the Southern Ocean, driving hotspots of productivity. Glacial meltwater fluxes can deliver high volumes of particulate iron. Here, we show that glacier meltwater provides particles rich in iron(II) to the Antarctic shelf surface ocean. Particulate iron(II) is understood to be more bioavailable to phytoplankton, but less stable in oxic seawater, than iron(III). Using x-ray microscopy, we demonstrate co-occurrence of iron and organic carbon-rich phases, suggesting that organic carbon retards the oxidation of potentially-bioavailable iron(II) in oxic seawater. Accelerating meltwater fluxes may provide an increasingly important source of bioavailable iron(II)-rich particles to the Antarctic surface ocean, with implications for the Southern Ocean carbon pump and ecosystem productivity.